DARI PETANI MENJADI NELAYAN: KAJIAN HISTORIS PERIKANAN TANGKAP PANTAI SELATAN YOGYAKARTA - Suadi Suadi (Universitas Gadjah Mada, 2002)
The aims of this research were to know the history and development of fisheries activity and its contribution to coastal community welfare at South Coast of Yogyakarta Special Territory Province. To examine these issues the research was conducted by combined survey and descriptive analytic methods. Fisheries in area could be categorized as new activity and historically community does not have a high dependency on marine capture fisheries. Fishers were farmers who become fisherman due to several reasons such as limitation of land and lack of other job opportunity. Since the activity began in the end of 1970’s at Baron, marine capture fisheries have altered income sources, improve community houses, and attracted young people as well as provide productivity activity for rural women. In the recent time, marine capture fishery has dispersed to all of Yogyakarta South Coastal area at 19 fish-landing places with vary intensity of resources exploitation. Marine capture fisheries are still limited in the coastal zone. Although CPUE tend to increase, the activity should be extended to province management zone and ZEEI. The integrated policy and management are needed to solve these problems and to avoid the tragedy of the commons.